# How do you multiply #(8x + 9)(8x + 3) #?

Collect like terms

Therefore,

By signing up, you agree to our Terms of Service and Privacy Policy

To multiply the expressions ((8x + 9)(8x + 3)), you can use the distributive property or the FOIL method.

Using the distributive property:

((8x + 9)(8x + 3) = 8x \times (8x + 3) + 9 \times (8x + 3))

Expanding each term:

(= 8x \times 8x + 8x \times 3 + 9 \times 8x + 9 \times 3)

(= 64x^2 + 24x + 72x + 27)

(= 64x^2 + (24x + 72x) + 27)

(= 64x^2 + 96x + 27)

Using the FOIL method:

((8x + 9)(8x + 3) = (8x \times 8x) + (8x \times 3) + (9 \times 8x) + (9 \times 3))

(= 64x^2 + 24x + 72x + 27)

(= 64x^2 + (24x + 72x) + 27)

(= 64x^2 + 96x + 27)

Therefore, the product of ((8x + 9)(8x + 3)) is (64x^2 + 96x + 27).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7